2017
DOI: 10.1063/1.4983206
|View full text |Cite
|
Sign up to set email alerts
|

Chemical etching of silicon carbide in pure water by using platinum catalyst

Abstract: Chemical etching of SiC was found to proceed in pure water with the assistance of a Pt catalyst. A 4H-SiC (0001) wafer was placed and slid on a polishing pad in pure water, on which a thin Pt film was deposited to give a catalytic nature. Etching of the wafer surface was observed to remove protrusions preferentially by interacting with the Pt film more frequently, thus flattening the surface. In the case of an on-axis wafer, a crystallographically ordered surface was obtained with a straight step-and-terrace s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…MRR was calculated from equation ( 15) by setting m=[-5,-4,-3,-2,-1], n= [1,2,3,4,5], RB= [15,30,45,60,75].…”
Section: Methodsmentioning
confidence: 99%
“…MRR was calculated from equation ( 15) by setting m=[-5,-4,-3,-2,-1], n= [1,2,3,4,5], RB= [15,30,45,60,75].…”
Section: Methodsmentioning
confidence: 99%
“…Pho Van Bui et al [64] studied the reaction mechanism of a Pt catalyst on single-crystal SiC etching in In early CARE studies, the catalyzed liquid medium was either HF or H 2 O 2 , which would cause adverse effects on the environment. In 2017, Ai Isohashi et al [63] found that a 3-inch 4H-SiC (0001) surface could still be polished in pure water under the action of a Pt catalyst with a certain electrochemical potential, and the etching mechanism was accelerated by hydrolysis under the action of Pt. In the study, OH − is considered to play the same role as F − in CARE, as shown in Figure 30b, and to proceed with an indirect dissociative adsorption of H 2 O (i.e., indirect hydrolysis).…”
Section: R Peer Review 20 Of 31mentioning
confidence: 99%
“…Because polishing parameters K and polishing pressure P were constants and initial angle 0 has no effect on MRR, in order to facilitate normalization of simulation analysis, we set K=1, P=1Pa, initial angle 0=0°, s=-20r/min, t=1s. Influence of the three parameters (speed rate of the outside ring gear to the inside sun gear m, speed rate of lower plate to the inside sun gear n, SiC substrate distribution radius RB) in formula (15) on MRR was studied.…”
Section: O2mentioning
confidence: 99%
“…MRR was calculated from equation ( 15) by setting m=[-5,-4,-3,-2,-1], n= [1,2,3,4,5], RB= [15,30,45,60,75].…”
Section: O2mentioning
confidence: 99%
See 1 more Smart Citation